Identifikasi Potensi Akuifer Menggunakan Metode Geolistrik Resistivitas Konfigurasi Wenner di Kelurahan Betungan, Kota Bengkulu - Felysia Laurend; Suhendra; Efmadani (Mataram University, 2026)
Groundwater is an important water resource for meeting community water demands. Information regarding subsurface characteristics and aquifer occurrence is essential for assessing groundwater potential in a given area. This study aims to identify subsurface layer characteristics and determine zones with potential as aquifers in Raflesia Asri Housing Estate, Betungan Village, Selebar District, Bengkulu City. The research employed the two-dimensional (2D) electrical resistivity method using the Wenner configuration. The measured data were processed using Res2DINV software to obtain a subsurface resistivity distribution model. The inversion results indicate resistivity values ranging from 1.52 Ωm to 317 Ωm, with an investigation depth of approximately 43 m. Low-resistivity zones (1.52–15.0 Ωm) are interpreted as clay and silt layers, whereas moderate-resistivity zones (15.0–69.0 Ωm) are interpreted as clayey sand to water-saturated sand, which are considered potential aquifer layers. High-resistivity zones (>69.0–317 Ωm) are interpreted as gravelly sand and weathered rock. The dominance of moderate-resistivity zones in the inverted resistivity sections indicates the presence of potential aquifers that may serve as groundwater resources in the study area.